Direct Election System for President and Vice President in Indonesia Post Amendment the Constitution of 1945 - Suparto Suparto (LEGAL BRIEF, 2022)
Indonesia has held 4 (four) direct elections for President and Vice President by the people after Amendment the Constitution of 1945. Of the 4 elections for President and Vice President, there is a difference in the 2019 election. In that year, the general election for the President and Vice President was held simultaneously with the Legislative election (elections for members of DPR, DPD, DPRD). This is different from the three previous elections, in the 2004, 2009 and 2014 elections, in which the general election for the President and Vice President was conducted after the Legislative election or not simultaneously. The general election for the President and Vice President in 2019 besides being carried out simultaneously, also still applies provisions regarding the minimum threshold (presidential threshold) for political parties to nominate a pair of President and Vice President as regulated in Article 222 of Law no. 7 of 2017 concerning Elections. Based on the research, it was found that the simultaneous election with the implementation of the presidential threshold resulted in the following points: (a). The occurrence of a non-ideal democratic system, because during the nomination stage for the presidential and vice-presidential pairs, the votes used by political parties or coalitions of political parties are the results of the previous period's legislative elections. Meanwhile, during the election stage for the pair of President and Vice President, the votes used are the results of the current year's election. (b). The existence of political parties that proposed pairs of candidates for President and Vice President did not qualify or did not obtain seats in the elections which were held simultaneously. Meanwhile, the pair of presidential and vice-presidential candidates he carried won the presidential and vice-presidential elections. c). Closing the opportunity for new parties to nominate pairs of candidates for President and Vice President, even though those parties are declared to have passed the selection (verification) and are designated as election participants by the General Elections Commission (KPU) because they do not have votes or seats because they have never participated in elections.